Special Audit of Medical Education Projects of Employees State Insurance Corporation (ESIC) - CAG of India (CAG of India, 2015)
"This Report contains the result of Special audit of Medical Education Projects of Employees’ State Insurance Corporation (ESIC) for the period 2008-09 to 2014-15. Employees’ State Insurance Scheme (ESIS) is an integrated social security scheme mandated to provide protection to workers and their dependants in the organized sector in contingencies such as sickness, maternity and death or disablement due to employment injury or occupational disease. The Government of India, Ministry of Labour and Employment in November 2014 requested the C&AG of India to conduct a special audit of 13 ongoing Medical Colleges Projects. It was specifically desired by the Ministry that the special audit may be taken up to address the following concerns • Whether due diligence was observed while deciding to take up medical education projects? • Whether these projects were able to fulfill the objectives envisaged under Section 59(B) of ESI Act? • Whether the provisions of General Financial Rules (GFRs) were followed while implementing these projects? The Ministry had requested the CAG to conduct special audit of 13 ongoing Medical Education Projects. We, however, noticed from the records that instead of 13 Medical Education Projects, ESIC had taken up setting up of 22 Medical Education Projects"
For the Period 2008-09 to 2014-15